Cosmetics utilization and its Knowledge among Intermediate Level Female Students of Public Youth Campus, Janakpurdham (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: Assorted beauty products such as skin care products, hair products, fragrances and nail products that may contain toxic chemicals and that can be harmful to health are especially used by women. The objective of this study was to assess the utilization of cosmetics and its knowledge among intermediate level female students.MATERIALS AND METHODS: The study was conducted at Public Youth Campus, Janakpurdham using descriptive cross-sectional study design. Purposive sampling technique was used. Intermediate level female students were included in the study. The data were analysed using IBM SPSS Version 23. Descriptive and inferential analysis was carried out to find out frequency and association between socio-demographic variables, and knowledge regarding the effects of cosmetics utilization.RESULTS: The study revealed that 53.8% of respondents had started using cosmetics at the age of 12-16 years, 20% of respondents had started using cosmetics at the age of 16-20 years, whereas 26.3% had started using cosmetics before the age of 12. Moreover, 68.8% of respondents believed that long-term usage of cosmetic products was beneficial whereas 31.2% of respondents had experienced the adverse effects of cosmetics utilization. Additionally, 28.7% of respondents had a high level of knowledge regarding cosmetics utilization.CONCLUSIONS: The study found that the knowledge regarding the effect of cosmetics utilization was moderate among the respondents. It was also found that the adverse effects of cosmetic use lead to allergic reactions and skin discoloration upon long term usage of cosmetic products. Health education program to the target population is crucial with focus on cosmetic use and its adverse effects on health.